Spatial-temporal analysis and risk characterisation of pesticides in Alpine glacial streams. (May 2019) - Rizzi, C.; Finizio, A.; Maggi, V.; Villa, S.
Abstract: We analysed the spatial and temporal distribution of a selection of pesticides in Alpine glaciers used on the Po Plain in Northern Italy, near the Alps. By analysing a 102-m ice core taken from the Lys Glacier (Monte Rosa massif, Italy), we highlight historical contamination from the insecticide chlorpyrifos and the herbicide terbuthylazine, confirming the role of alpine glaciers as temporal sinks. In addition, we collected meltwater samples from six glaciers distributed along the Alpine Arc during the summer of 2016, which showed widespread contamination by pesticides. Overall, chlorpyrifos and terbuthylazine dominated the contaminant fingerprint of all of the studied glaciers, with contamination peaks occurring at the beginning of the melting season. This highlights the importance of the medium-range atmospheric transport of these pesticides in connection with agricultural practices in the areas beneath the Italian Alps, where they are widely applied. The release of pesticides in meltwater can lead to potential risks to the aquatic ecosystems of headwater streams, as we demonstrate for chlorpyrifos. This suggests that the medium-range atmospheric transport of pesticides should be considered as part of regulations to protect the water quality of these pristine environments. Graphical abstract: Image 1 Highlights: Chlorpyrifos was detected in all glacial meltwater from Alpine Glaciers. Terbuthylazine and its metabolite detected in glaciers closer to Po plain. Chlorpyrifos and terbuthylazine concentrations in ice core vary with sale volumes. Risk characterisation of chlorpyrifos indicates concern for alpine aquatic species.